AB1362-HPR COMMON PRACTICE IN DELIVERY OF INTRA-ARTICULAR THERAPIES IN RMDS BY HEALTH PROFESSIONALS: RESULTS FROM A EUROPEAN SURVEY. (13th June 2020) - De la Torre-Aboki, J.; Pitsillidou, I.; Uson Jaeger, J.; Naredo, E.; Terslev, L.; Boesen, M.; Pandit, H.; Möller, I.; D'agostino, M. A.; Kampen, W. U.; O'neill, T.; Doherty, M.; et al.
Abstract : Background: Intra-articular therapies (IAT) are routinely used in rheumatic and musculoskeletal diseases (RMDs); however large variability exists regarding current practice of delivery amongst health professionals. Objectives: To inquire about common practice aspects to inform the EULAR Taskforce for the IAT of arthropathies. Methods: A steering committee prepared a 160-item questionnaire based on the information needs of the Taskforce. The survey was disseminated via EULAR professional associations and social media and it was open to any health professional treating persons with RMDs, regardless of using IAT personally. Results: The survey was answered by 186 health professionals from 26 countries, the large majority of whom (77%) were rheumatologists, followed by nurses (12%), general practitioners (2%) and orthopaedic surgeons (2%). The two collectives that perform IAT routinely are rheumatologists (97%) and orthopaedic surgeons (89%), with other professionals <50%. Specific training was compulsory for 32%. The most frequent indication for IAT is inflammatory arthritis (76%), followed by osteoarthritis (74%), crystal arthritis (71%) and bursitis (70%); and all joints are injected, with knee (78%) and shoulder (70%) being the most frequent. When questioned about specific contexts, such as pre-surgical, diabetic or hypertensive patients, variability among respondents was evident, with around 30 to 69% of professionals considering it acceptable to inject glucocorticoids (GC), while in others there was less variability (prosthetic or septic joints, <1%). GCs are the most used compounds, followed by hyaluronic acid and saline/dry puncture. Only 66 (36%) use ultrasound to guide IAT. In their opinion, to be accurately in the joint is moderately to largely important for large joints (80%) and very important in small joints. The maximum number of injections to perform safely in the same joint within one year was "2 to 3" for 65% (2% thought there is "No limit"). The majority reported that they informed patients about side-effects (73%), benefits (72%), and the nature of the procedure (72%), and less frequently about other aspects; with 10% obtaining written consent and 56% oral consent (mandatory only for 32%). Other questions help to understand the setting and procedures followed, including use of local anaesthetics and care after injection. Conclusion: Although often performed in clinical practice for RMDs, there is apparent variability in several elements related to delivery of this treatment. This information, together with patient input, will help design current recommendations where research evidence is not available. Acknowledgments: Eular Taskforce grant CL109 Disclosure of Interests: Jenny de la Torre-Aboki: None declared, IRENE Pitsillidou: None declared, Jacqueline Uson Jaeger: None declared, Esperanza Naredo: None declared, Lene Terslev: None declared, Mikael Boesen Consultant of: AbbVie, AstraZeneca, Eli Lilly, Esaote, Glenmark, Novartis, Pfizer, UCB, Paid instructor for: IAG, Image Analysis Group, AbbVie, Eli Lilly, AstraZeneca, esaote, Glenmark, Novartis, Pfizer, UCB (scientific advisor)., Speakers bureau: Eli Lilly, Esaote, Novartis, Pfizer, UCB, Hemant Pandit Grant/research support from: Glaxo Smith Kline (GSK) for work on Diclofenac Gel, Speakers bureau: Bristol Myers Squibb for teaching their employees about hip and knee replacement, Ingrid Möller: None declared, Maria Antonietta D'Agostino Consultant of: AbbVie, BMS, Novartis, and Roche, Speakers bureau: AbbVie, BMS, Novartis, and Roche, Willm Uwe Kampen: None declared, Terence O'Neill: None declared, Michael Doherty Grant/research support from: AstraZeneca funded the Nottingham Sons of Gout study, Consultant of: Advisory borads on gout for Grunenthal and Mallinckrodt, Francis Berenbaum Grant/research support from: TRB Chemedica (through institution), MSD (through institution), Pfizer (through institution), Consultant of: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Bone Therapeutics, Regulaxis, Peptinov, 4P Pharma, Paid instructor for: Sandoz, Speakers bureau: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Sandoz, Valentina Vardanyan: None declared, Elena Nikiphorou: None declared, Sebastian C Rodriguez-García Speakers bureau: Novartis Farmaceutica, S.A., Merck Sharp & Dohme España, S.A., Sanofi Aventis, UCB Pharma, Raul Castellanos-Moreira: None declared, Loreto Carmona Grant/research support from: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution)